Educators' use of questioning as a pedagogical strategy in long day care nurseries. Issue 1 (2nd January 2016) - Davis, Belinda; Torr, Jane
Abstract : Educators' questions can encourage children to engage in extended conversations, facilitate comprehension and stimulate thinking. Many studies of educators' questioning have focused on children aged 3 years and older. Little is known about the manner in which educators of infants in non-parental group care settings use questioning as a pedagogical strategy. Six university-qualified early childhood educators in Sydney, Australia, were videorecorded for 40 min each in their long day care centres. Informed by systemic functional linguistic theory, the educators' questions addressed to infants (defined as children under 2 years of age) were coded according to whether they served a pedagogical or regulatory function. Pedagogical questions were defined as questions intended to promote children's learning, whereas regulatory questions functioned as commands and offers which were intended to manage behaviour. The educators' pedagogical questions were then further analysed according to the response required of the infant. Confirm questions sought a yes or no response, specify questions (who, when, where, what) sought the name of a person, time, place or entity and explain questions (why or how) sought an explanation or justification. The findings demonstrated that educators differed greatly in terms of the frequency and manner in which they used questioning as a pedagogical strategy when interacting with infants. So-called open questioning, which has been shown to stimulate conversation with older children, may not be appropriate for infants whose distinctive developmental trajectories differ from those of preschool-aged children. The findings suggest the need for a more nuanced understanding of the role of questioning in promoting infants' language, literacy and intellectual development.